Workforce Capacity and Operational Processes on Delivery of Healthcare Services in Zambia: A Case of Chikuni Mission Hospital in Monze District - Kanyamuna, Vincent; Muyunda, Cecilia (Advances in Social Sciences Research Journal, 2026)
This study aimed to assess the Public Service Delivery Performance (PSDP) systems at Chikuni Mission Hospital in Monze District, Southern Province, Zambia. Utilizing a qualitative case study design, the research employed a purposive sampling method to select 20 participants, including healthcare professionals, support staff, and administrators, who provided insights into the hospital’s service delivery dynamics. Data was collected through interviews and review of existing literature. Data was analysed thematically. Zambia’s [12] aims to achieve equitable access to quality healthcare for all by 2030. However, [19] highlights persistent challenges in the healthcare sector, including inconsistent supply of essential medical supplies, shortages of health personnel, and ineffective management of Non-Communicable Diseases (NCDs). Rural areas, such as Chikuni, face even greater barriers to healthcare access due to low health-seeking behaviors, limited healthcare workforce, long distances to health facilities, inadequate medical supplies, and a shortage of specialists to handle complex cases. The study focused on Chikuni Mission Hospital and aimed to assess the workforce capacity in delivering healthcare services and evaluate the effectiveness of operational processes in improving public service delivery at the hospital. The study revealed inadequate medical equipment, and inconsistent supply chains, which compromise the quality of healthcare delivery. Workforce issues, such as staffing shortages and gaps in specialized skills, further strained the hospital’s capacity to manage patient care effectively. Despite the hospital’s commitment to improving service delivery through systems like electronic health records (smart care) and centralized pharmacy management, inadequate staff training hindered the full utilization of these systems. The study concluded that Chikuni Mission Hospital requires urgent interventions to address these challenges. Further, the study revealed critical staffing shortages and a lack of specialized skills, which place additional strain on existing healthcare workers. Overburdened staff often experience burnouts and reduced efficiency, leading to compromised patient care. The study concludes that without modern and well-maintained, healthcare providers struggle to deliver timely and effective treatment, potentially leading to delays in diagnosis, increased patient referrals, and higher mortality rates. The inconsistent supply chain further exacerbates these issues, as a lack of essential medical supplies can disrupt treatment plans, leaving patients without necessary medications or equipment. Recommendations include recruiting additional healthcare professionals, and enhancing training programs. Implementing these changes is essential for improving service delivery and ensuring the hospital can meet the healthcare needs of its community effectively.